Prakash's notebook of microbiology : Including parasitology and entomology for undergraduate students and PG aspirant /s - Modi, Prakash (CBS Publishers, 2017)
This is an ideal textbook and handbook on microbiology for undergraduate medical students, as well as a guide for candidates preparing for postgraduate entrance examinations.Written in a bulleted/point-wise style, it offers a simplistic approach to learning, memorizing and mastering the subject for attaining significant achievement. Prepared according to the MCI syllabus, it hosts a large number of key/salient features for the student with a clear approach to clinical microbiology. Two associated topics parasitology and entomology have been covered in detail.